The Local Sanarelli-Shwartzman Phenomenon in Rats Induced by Human Leukaemic Cells - Lisiewicz, J; Pituch, A; Litwin, J. A (Thrombosis and Haemostasis, 1973)
The local Sanarelli-Shwartzman phenomenon (SSP-L) in the skin of 30 rats was induced by an intr a cutaneous sensitizing injection of leukaemic leucocytes isolated from the peripheral blood of patients with chronic lymphocytic leukaemia (CLL), acute myeloblastic leukaemia (AL) and chronic granulocytic leukaemia (CGL) and challenged by an intravenous injection of 100(μ of E. coli endotoxin. SSP-L was observed in 7 rats after injection of CLL lymphocytes and in 6 and 2 rats after AL myeloblasts and the CGL granulocytes, respectively. The lesions in the skin after AL myeloblasts appeared in a shorter time and were of longer duration compared with those observed after CLL lymphocytes and CGL granulocytes. Histologically, the lesions consisted of areas of destruction in the superficial layers of the skin ; the demarcation line showed the presence of neutrophils, macrophages and erythrocytes. Haemorrhages and fibrin deposits near the demarcation line were larger after injection of CLL lymphocytes and AL myeloblasts than after CGL granulocytes. The possible role of leucocyte procoagulative substances in the differences observed have been discussed.